Hyptic, Body and Landscape in three key films of Portuguese cinema - Silveirinha Castello Branco, Patrícia (2019)
In this essay I will try and develop the concept of haptic visuality, departing from three important films of the history of Portuguese Cinema: The Dance of the Paroxysms (Jorge Brum do Canto, 1929), Change of Life (Paulo Rocha, 1967) and The Zone (Sandro Aguilar, 2008). I will begin with an introduction to the concept of haptics, as Alois Riegl originally conceived it. Next, I will engage in a specific analysis of the above films, starting with Brum do Canto’s The Dance of the Paroxysms. I will try and examine the unique relationship Brum do Canto establishes between haptic visuality and the subversion of Portuguese rural landscape. I will proceed with an analysis of Paulo Rocha’s Change of Life, focusing on what I consider to be the main aesthetic element of the work: the composition of a space that dwells in a continuous passage between physical relations with reality and emotional and social ones. I will conclude with a brief examination of Sandro Aguilar's The Zone, trying to assess how this film incorporates practices typically denoted as haptic, a concept that I will once again try and develop.